Inrein App: Spice Detector Using Smartphone Camera Sensor - Bobi Kurniawan; Weldira Tarigan; Hafid Ramadhan; Muhammad Hadyan Nur Adabi (Universitas Komputer Indonesia, 2022)
Indonesia is a very abundant spice-producing country, but not many people know the types of spices due to lack of information. The purpose of this research is to design a mobile-based application that functions as a platform for providing information about spices in Indonesia. The research method used in this study is descriptive analysis with a qualitative approach, while in the process of developing the application using a camera sensor on a smartphone. The results of the study indicate that the Inrein application development can provide information on spices using a digital platform that can be accessed through their respective smartphones. The main concept of this application is the introduction of types of spices to information on the location and use of these types of spices. In addition, this application also has a feature that can provide information on the management of spice ingredients into healthy food or drinks from spices that are detected by the user's camera sensor. The conclusion of the application that we made is able to help users to get information, manage and also benefit from spices.